Impairments of Speech Comprehension in Patients with Tinnitus—A Review - Ivansic, Daniela; Guntinas-Lichius, Orlando; Müller, Boris; Volk, Gerd F.; Schneider, Gerlind; Dobel, Christian (Frontiers in Aging Neuroscience, 2017)
Tinnitus describes the subjective perception of a sound despite the absence of external stimulation. Being a sensory symptom the majority of studies focusses on the auditory pathway. In the recent years, a series of studies suggested a crucial involvement of the limbic system in the manifestation and development of chronic tinnitus. Regarding cognitive symptoms, several reviews addressed the presence of cognitive impairments in tinnitus as well and concluded that attention and memory processes are affected. Despite the importance for social communication and the reliance on a highly functional auditory system, speech comprehension remains a largely neglected field in tinnitus research. This is why we review here the existing literature on speech and language functions in tinnitus patients. Reviewed studies suggest that speech comprehension is impaired in patients with tinnitus, especially in the presence of competing noise. This is even the case in tinnitus patients with normal hearing thresholds. Additionally, speech comprehension measures seem independent of other measures such as tinnitus severity and perceived tinnitus loudness. According to the majority of authors the speech comprehension difficulties arise as a result of central processes or dysfunctional neuroplasticity.